Building a supportive workplace. (23rd September 2022) - Read, Claire
Abstract: As veterinary practices up and down the country prepare to take part in Macmillan's Coffee Morning, Victoria Bowes tells Claire Read about her experience with cancer – and the importance of workplaces supporting those experiencing ill health.